Daya Tarik Organisasi di Perusahaan E-Commerce dan Dampaknya Pada Niat Melamar Kerja - Hastuti Naibaho; Cindy Malinda Uscha (Universitas Negeri Surabaya, 2025)
Globalization has significantly intensified business competition, with multinational corporations emerging as major contenders in increasingly open global markets. This development affects not only competition for consumers but also the competition to attract and retain competent employees with strong work ethics. E-commerce is a sector characterized by high market demand and a substantial contribution to current economic growth. Job seekers’ willingness to join a company is shaped by perceived organizational attractiveness. The study aims to analyze the influence of organizational attractiveness dimensions, including organizational attributes, experiences of responsibility, knowledge of results, and work meaningfulness, on job application intentions at e-commerce companies in Indonesia. A quantitative research method is used by using a survey. Data were collected through a Likert-scale questionnaire distributed online. The sampling technique used was purposive sampling, with 132 respondents. Data analysis was performed using multiple linear regression for hypothesis testing. The results show that organizational attributes, experiences of responsibility, and work meaningfulness have a positive and significant effect on job application intentions at e-commerce companies. In contrast, knowledge of results did not significantly influence job application intentions. This research provides theoretical contributions to the development of the literature on organizational attraction and person–organization fit, as well as practical contributions for e-commerce companies in designing recruitment strategies to build a competitive talent pool.